Efektifitas Elevasi Kepala 300 Dalam Meningkatkan Perfusi Serebral Pada Pasien Post Trepanasi di Rumah Sakit Mitra Surabaya - Huda, Nuh (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Head trauma often causes cerebral perfusion disturbances that can cause some problems. Conditions of hypoxia, hypercapnia, hypotension and cerebral edema can cause further effect is increased intracranial pressure due to an increase in a confined space, reduced cerebral perfusion. so necessary actions to improve perfusion is by setting position of the head elevation 300 to increase cerebral venous drainage. The purpose of this study was to analyze the effectiveness of a 30° head-up positionin the post trepanation head injury patients in improving cerebral perfusion. This study used anonqui valent control group design. Post-op patient population trepanation head trauma in Hospital Mitra Keluarga Surabaya at 1 month Desember 2012 – 10 February 2013. The sample of the study15 patients with post-op trepanation head trauma. Sampling was done by purposive sampling technique. The variables of this study is the head-up 300 in patients post-op trepanation head trauma and cerebral perfusion. The results showed that the average MAP was100 mmHg and average GCS was 12.4. Based on the test paired t-test with significance level α=0.005 obtained P= 0.000 means there is influence the effectiveness of the head-up 300 against cerebral. Perfusionin patients with post-op trepanation after 8 hours. Head up to 300 can improve cerebral perfusion in patients with head trauma post op trepanation. This research needs to be recommended to the health practitioner, specializing in nursing to provide ahead-up position 300 to increase cerebral perfusion. Keywords: Flat Position, Head Up 300, Post Op Trepanation Head Trauma and Cerebral Perfusion.